Whole-cell cAMP and PKA activity are epiphenomena, nanodomain signaling matters - Bers, DM; Xiang, YK; Zaccolo, M (American Physiological Society, 2019)
Novel targeted fluorescent biosensors provide key insights into very local nanodomains of cAMP and PKA activity, and how they respond differently to β-adrenergic activation in cardiac myocytes. This unique spatiotemporal detail in living cells is not available with biochemical measurements of total cellular cAMP and PKA, and provides unique physiological insights.